THE DEPICTION OF GENERAL PHYSICIAN’S KNOWLEDGE LEVEL OF PARKINSON’S DISEASE IN INDONESIA - Neila Raisa; Adeliza Firzarosany Insanitaqwa; Masruroh Rahayu (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2023)
Background: Parkinson's disease still requires special attention considering that this condition is a progressive disease that leads to a decrease in the quality of life and life expectancy of the patient. Objective: This study aims to determine the level of understanding of general practitioners regarding Parkinson's disease and other movement disorders. Methods: We conducted a one group pretest posttest design study on 124 general practitioners who attended the World Parkinson Day Seminar. . The research instrument was a questionnaire with 20 questions, filled in by the participants independently. Knowledge level categories are good (76-100), sufficient (56-75), and poor (<55). Results: The result of the study showed that 18% [22 respondents] had a good level of understanding, 58% [72 respondents] had sufficient knowledge, and 24% [30 respondents] had poor knowledge in terms of the pretest score. There was an increase in the average score (from 65.93 to 78.9) of the respondents after attending the seminar (p<0.05). Conclusion: This study identified that there was a significantly increased level of knowledge of Parkinson's disease symptoms after the seminar for general practitioners in Indonesia.